Association between cognitive vulnerability, dental fear, and oral health status among schoolchildren in Bangalore city - A cross-sectional study - Santhiya Bairappan; Manjunath P Puranik; Namita Shanbhag (Wolters Kluwer Medknow Publications, 2020)
Context: Dental anxiety and fear is not only a psychological problem but also a dental health problem. It is important to understand how the cognitive elements influence child's dental anxiety/fear and interact with their oral health. Objective: This study was conducted among children to determine the association between cognitive vulnerability (CV) with dental fear and their oral health status. Settings and Design: A cross-sectional study was conducted among 500 schoolchildren aged 12-15 years in Bengaluru city. Methodology: The schools and participants were selected by cluster random and systematic random sampling method, respectively. Cognitive vulnerability and Index of Dental Anxiety and Fear (IDAF-4C+) were assessed by a self-administered questionnaire. Oral health status was recorded using the World Health Organization 2013 proforma for children. Statistical Analysis Used: Chi-square test, Student's t-test, Spearman's correlation, and multivariate hierarchical linear regression were used in this study. The statistical significance was considered at P < 0.05. Results: Nearly half of the study participants had cognitive perceptions, dental anxiety/fear, phobia, and stimulus toward dental treatment. Majority had dental caries and gingival bleeding. Cognitive vulnerability, dental anxiety/fear, phobia, and stimulus were independent of the age and gender and were associated with socioeconomic status. A significant correlation was found between participants' CV, IDAF-4C+, dental caries, and gingival bleeding. Cognitive vulnerability was a significant predictor of dental caries and gingival bleeding. Dental anxiety/fear and dental phobia were significant predictors of dental caries. Conclusion: Oral health status was significantly poorer and was associated with CV, dental anxiety/fear, phobia, and stimulus. Cognitive elements together with dental fear influenced oral health.